Swedish election study 1968 - Särlvik, Bo; Statistics Sweden (University of Gothenburg, 1982)
The 1968 election study is almost twice as big as the earlier election studies, largely because of the goal of the survey, which was to cover the system of representation. A separate study, addressed to the Members of Parliament, included similar questions put in this study of the electorate. In this way a comparison of the opinions of the electorate and the opinions of the MP´s is possible. Except the questions repeated in all election studies, this study includes questions on employment, public representation on bank boards, agricultural policy, income tax, privately-owned TV-companies, religion, aid to developing countries, defence expenditures, and the Common Market. There are also a number of questions about how different groups are treated by the authorities. It also includes questions about the respondent´s sympathies for different groups in society. This study also introduces the left-right scale, a ten degree scale on which the respondent positions the political parties according to the respondent´s opinion of the party as a left-wing, centre or right-wing party. The 1968 study is the second stage in the 1964-1968-1970 panel study.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

The 1968 election study is almost twice as big as the earlier election studies, largely because of the goal of the survey, which was to cover the system of representation. A separate study, addressed to the Members of Parliament, included similar questions put in this study of the electorate. In this way a comparison of the opinions of the electorate and the opinions of the MP´s is possible. Except the questions repeated in all election studies, this study includes questions on employment, public representation on bank boards, agricultural policy, income tax, privately-owned TV-companies, religion, aid to developing countries, defense expenditures, and the Common Market. There are also a number of questions about how different groups are treated by the authorities. It also includes questions about the respondent´s sympathies for different groups in society. This study also introduces the left-right scale, a ten degree scale on which the respondent positions the political parties according to the respondent´s opinion of the party as a left-wing, center or right-wing party. The 1968 study is the second stage in the 1964-1968-1970 panel study.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1968
VU68
Keywords: developing countries; utvecklingsland; elections; val; housing; boende; mass media; massmedia; defence; försvar; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; religion; religion; social mobility; social rörlighet; regionalism; regionalism; ethics; etik; international relations; internationella relationer; voting; röstning; taxation; beskattning; internal politics; inrikespolitik; political parties; politiska partier; trade unions; fackföreningar; organizations; organisationer; farming; jordbruk; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Political ideology; Politisk ideologi; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap